2012
DOI: 10.1007/s12032-012-0227-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of vascular endothelial growth factor (VEGF) tyrosine kinase inhibitor (TKI) and mammalian target of rapamycin (mTOR) inhibitor as second-line therapy in patients with metastatic renal cell carcinoma after the failure of first-line VEGF TKI

Abstract: Sequential therapy is a standard strategy used to overcome the limitations of targeted agents in metastatic renal cell carcinoma. It remains unclear whether a mammalian target of rapamycin (mTOR) inhibitor is a more effective second-line therapy after first-line vascular endothelial growth factor tyrosine kinase inhibitor (VEGF TKI) has failed than the alternative, VEGF TKI. A clinical database was used to identify all patients with renal cell carcinoma who failed at first-line VEGF TKI and then treated with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 23 publications
1
31
1
Order By: Relevance
“…In a study of US claims data, Chen et al (2012) 29 reported that secondline everolimus was associated with the lowest risk of treatment failure when compared to temsirolimus and sorafenib (HR for temsirolimus versus everolimus was 2.05; 95% CI 30 found that a first-line VEGF inhibitor followed by a second-line mTOR inhibitor was associated with a numerically lower hazard of death when compared to treatment with a first-line VEGF TKI followed by a second-line VEGF TKI, after adjusting for the Heng prognostic score, clear cell histology, and nephrectomy status. Although the present study did not identify a statistically significant difference in OS between everolimus and TKIs, the 95% confidence interval for the hazard ratio is wide and does not indicate any inconsistency with the findings of Heng et al Though other retrospective studies comparing the use of TKIs versus mTORs in a second-line setting exist 24,28,[31][32][33][34] , it is not clear that the findings can be compared, due to the main limitation of sample size for these studies (and some other study design and analysis limitations -for example, Iacovelli et al (2014) 34 only included patients who have received three lines of treatment, which introduced a significant selection bias).…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…In a study of US claims data, Chen et al (2012) 29 reported that secondline everolimus was associated with the lowest risk of treatment failure when compared to temsirolimus and sorafenib (HR for temsirolimus versus everolimus was 2.05; 95% CI 30 found that a first-line VEGF inhibitor followed by a second-line mTOR inhibitor was associated with a numerically lower hazard of death when compared to treatment with a first-line VEGF TKI followed by a second-line VEGF TKI, after adjusting for the Heng prognostic score, clear cell histology, and nephrectomy status. Although the present study did not identify a statistically significant difference in OS between everolimus and TKIs, the 95% confidence interval for the hazard ratio is wide and does not indicate any inconsistency with the findings of Heng et al Though other retrospective studies comparing the use of TKIs versus mTORs in a second-line setting exist 24,28,[31][32][33][34] , it is not clear that the findings can be compared, due to the main limitation of sample size for these studies (and some other study design and analysis limitations -for example, Iacovelli et al (2014) 34 only included patients who have received three lines of treatment, which introduced a significant selection bias).…”
Section: Discussioncontrasting
confidence: 91%
“…Note that, in Europe, temsirolimus is approved only ''for the first-line treatment of adult patients with advanced renal cell carcinoma (RCC) who have at least three of six prognostic risk factors'' 19 . While multiple second-line treatment options are available for mRCC, evidence for the comparative efficacy of these agents is limited 7,9,11,[20][21][22][23][24][25] . Due to the rapid emergence of multiple targeted agents within the past 8 years, comparative data from clinical trials is limited (and may never occur due to the cost of such trials).…”
Section: Introductionmentioning
confidence: 99%
“…Several retrospective studies have described the real-world treatment patterns and outcomes of different second-line therapies following TKI failure [14][15][16][17][18][19] . However, these studies focused on a subset of patient populations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, complete and durable responses have been noted in only a few cases (Buczek et al , 2014). Furthermore, 26% out of 1056 patients treated with sorafenib and sunitinib were primarily refractory to treatment (Park et al , 2012). …”
mentioning
confidence: 99%